Evidence for serum miR-15a and miR-16 levels as biomarkers that distinguish sepsis from systemic inflammatory response syndrome in human subjects - Wang, Huijuan; Zhang, Pengjun; Chen, Weijun; Feng, Dan; Jia, Yanhong; Xie, Li-xin (Clinical chemistry and laboratory medicine, 2012)
: Serum microRNAs may be useful biomarkers for diagnosing human diseases. We investigated serum levels of miR-15a and miR-16 in patients with sepsis and systemic inflammatory response syndrome (SIRS) without infection. : We enrolled 166 sepsis patients, 32 SIRS patients, and 24 normal controls. Serum miR-15a and miR-16 expression levels were determined by quantitative reverse transcriptase polymerase chain reaction assays (qRT-PCR). : Serum miR-15a (p<0.001) and miR-16 (p<0.05) were both significantly higher in sepsis patients compared with normal controls, and miR-15a (p<0.001) and miR-16 (p<0.01) levels in SIRS patients were also significantly higher than those in normal controls. Serum miR-15a and miR-16 levels were not correlated with white blood cell counts. Receiver operating characteristic curves showed that miR-15a had the highest area under the curve of 0.858 [95% confidence interval (CI) 0.800–0.916] for the diagnosis of sepsis compared with C reactive protein and procalcitonin with areas under the curve of 0.572 (95% CI 0.479–0.665; p=0.198) and 0.605 (95% CI 0.443–0.767; p=0.168), respectively. When its cut-off point was set at 0.21, serum miR-15a had a sensitivity of 68.3% and a specificity of 94.4%. : Serum miR-15a and miR-16 can both distinguish sepsis/SIRS from normal controls. miR-15a may be a biomarker that distinguishes between sepsis and SIRS.